1993
DOI: 10.1021/bp00022a002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oxygen/Glucose/Glutamine Feeding on Insect Cell Baculovirus Protein Expression: A Study on Epoxide Hydrolase Production

Abstract: The recombinant protein yields for batch cultures of the insect cell baculovirus expression system have been significantly enhanced by oxygen, glucose, and glutamine feeding. The improvement in both volumetric and specific yields was based on influencing the metabolism of infected cells. Oxygen was absolutely required for viral replication and high protein expression in infected cells. Increases of 200% in volumetric yield and 100% in specific yield of recombinant epoxide hydrolase were achieved by controlling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0
3

Year Published

1996
1996
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(54 citation statements)
references
References 14 publications
3
48
0
3
Order By: Relevance
“…Thus, an infection performed close to the maximum concentration (as the infection in the late exponential phase) will most probably induce a situation of oxygen depletion and decrease the infection efficiency due to the increase in the specific oxygen uptake rate caused by cell infection (Agathos, 1996). Other authors have also reported reduced productivities and considerably lower rates of cell death for cells infected in the late exponential or in the stationary growth phase (Caron et al, 1990, Wang et al, 1993, in agreement with Figure 3.…”
Section: Effect Of Moi and Toi On Cell Infectionsupporting
confidence: 83%
See 1 more Smart Citation
“…Thus, an infection performed close to the maximum concentration (as the infection in the late exponential phase) will most probably induce a situation of oxygen depletion and decrease the infection efficiency due to the increase in the specific oxygen uptake rate caused by cell infection (Agathos, 1996). Other authors have also reported reduced productivities and considerably lower rates of cell death for cells infected in the late exponential or in the stationary growth phase (Caron et al, 1990, Wang et al, 1993, in agreement with Figure 3.…”
Section: Effect Of Moi and Toi On Cell Infectionsupporting
confidence: 83%
“…The insect cell / baculovirus system has been widely used in the production of several other proteins (Agathos 1996;Wang et al, 1993). Its main advantages include the capacity to perform posttranslational modifications, essential for HIV core-and virus-like particle production (such as myristylation and phosphorilation in the case of Pr55gag [Overton et al, 1989]), high productivities (both for cells and expressed product), and the ability to produce proteins with complex quaternary structures.…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies have been conducted in which nutrients were added a limited number of times (usually only once) over the course of the Sf-9 cell culture (Bedard et al, 1994;Drews et al, 1995;Nguyen et al, 1993;Reuveny et al, 1993b;Wang et al, 1993a). Wang et al (1993a) found that glutamine and glucose addition resulted in enhanced cell growth and recombinant protein productivity.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have been performed with the purpose of improving insect cell culture media formulation (Wilkie et al 1980;Mitsuhashi 1989;Wang et al 1993;Drews et al 1995;Schlaeger 1996;Vaughn and Fan 1997;Ikonomou et al 2001;Maranga et al 2003, Marteijn et al 2003. The efforts to eliminate bovine serum resulted in several commercially available serum-free media for insect cells, however, many of these media present very high costs and still require supplementation with other complex components such as protein hydrolysates.…”
Section: Introductionmentioning
confidence: 99%